The black belt librarian : real world safety & security - Graham, Warren Davis (American Library Association, 2012)
Sharing expertise gleaned from more than two decades as a library security manager, the author demonstrates that libraries can maintain their best traditions of openness and public access by creating an unobtrusive yet effective security plan. In straightforward language, the author: Shows how to easily set clear expectations for visitors' behavior; Presents guidelines for when and how to intervene when someone violates the code of conduct, including tips for approaching an unruly patron; Offers instruction on keeping persistent troublemakers under control or permanently barred from the library; and Gives library staff tools for communicating effectively with its security professionals, including examples of basic documentation. Also, this guide arms librarians with the confidence and know how they need to maintain a comfortable, productive, and safe environment for everyone in the library